2016
DOI: 10.1186/s13568-016-0282-0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning a novel endo-1,4-β-d-glucanase gene from Trichoderma virens and heterologous expression in E. coli

Abstract: Endo-1,4-β-d-glucanase (EG), as a key constituent of cellulase taking the responsibility of cutting β-1,4 glycosidic bonds, plays the essential role in the process of degrading cellulose by cellulase. Cloning and expressing the EG gene is important to the cellulase research and application. In this work, a novel EG gene was cloned from Trichoderma virens ZY-01, which was a cellulase secreting microbe isolated by our laboratory. The DNA sequence showed that the length of the cloned EG is 1069 bp, which had 95.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(33 reference statements)
0
11
1
Order By: Relevance
“…Cellulose as the main component of plant cell wall consists of linear long chains of β-1, 4 glucose units. Hydrolyzing cellulose by cellulase is ideal and promising for its utilization in environmentally friendly and high efficiency manner [2]. However, the cooperative action of three kinds of cellulolytic enzymes (endo-glucanase, exo-glucanase, and β-glucosidase) is essential in hydrolysis of cellulose to glucose [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose as the main component of plant cell wall consists of linear long chains of β-1, 4 glucose units. Hydrolyzing cellulose by cellulase is ideal and promising for its utilization in environmentally friendly and high efficiency manner [2]. However, the cooperative action of three kinds of cellulolytic enzymes (endo-glucanase, exo-glucanase, and β-glucosidase) is essential in hydrolysis of cellulose to glucose [3].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst fungal sources of cellulase gene, different strains of Trichoderma were widely studied. Zeng et al [ 26 ] reported cloning and expression of endo-(1,4)-β-D-glucanase gene from T. virens and disulphide bond formation was achieved by using pET32a vector. In another study, Okada et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the presently used endoglucanases, especially fungal endoglucanase, usually displayed their highest activity at acidic condition. Their activities are greatly reduced in case of the pH value above 7.0, limiting the application of those fungal enzymes under neutral and alkaline condition (Wang et al, 2014;Zeng et al, 2016;Ibrahim et al, 2017). Therefore, there has a large market and great demand for the endoglucanases which can be eff ective at broad pH with high activity.…”
Section: Discussionmentioning
confidence: 99%
“…carotovorum (Pcc) showed a pH optimum of 6.0 (Ibrahim et al, 2017), AcCel12B (GH12) from Acidothermus cellulolyticus 11B remained less than 10% of max enzyme activity at pH 7.0 (Wang et al, 2015). Especially, the neutral endoglucanase EgH31 showed outstanding stability in wide pH ranging from 3.0 to 11.0, and remained more than 70% of peak activity between pH 6.0 and 9.0, while most endoglucanases reported did not functionally work under the wide range of pH (Galante et al, 1998;Bhat, 2000;Trivedi et al, 2011;Yang et al, 2016;Zeng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%